The Effect of Mobile eHealth Education to Improve Knowledge, Skills, Self-Care, and Mobile eHealth Literacies Among Patients With Diabetes: Development and Evaluation Study - Sophie Huey-Ming Guo; Jiun-Lu Lin; Hung-Chun Hsing; Chun-Chuan Lee; Shih-Ming Chuang (JMIR Publications, 2023)
BackgroundThe promotion of mobile health (mHealth) and eHealth technologies as tools for managing chronic diseases, particularly diabetes mellitus, is on the rise. Nevertheless, individuals with diabetes frequently face a literacy gap that hinders their ability to fully leverage the benefits offered by these resources. Enhancing technology literacy to facilitate the adoption of mobile eHealth services poses a significant challenge in numerous countries. ObjectiveThis study aims to develop an educational mobile eHealth literacy (eHL) program for patients with diabetes and to evaluate its effect on patients' outcomes. MethodsThis study designed a mobile eHL education program comprising 2 modules specifically tailored for individuals with type 2 diabetes (T2D). These modules focused on guiding participants through the process of effectively navigating reliable health websites and utilizing diabetes-related apps. Using a pre- and posttest experimental design, the study featured an intervention group and a control group. Participants were recruited from 3 outpatient departments in hospitals, and assessments were conducted both before and after the intervention, along with a follow-up measure at the 3-month mark. The evaluation encompassed sociodemographic characteristics, computer and internet proficiency, mobile app usage, mobile eHL, and patient outcomes such as self-care behaviors and glycated hemoglobin (HbA1c) levels. ResultsThe analysis included a total of 132 eligible participants. Significant differences were observed in the mean scores of knowledge (P<.001) and skills (P<.001) related to computers, the web, and mobile devices at the initiation of the study and after the intervention. During the 3-month follow-up, the findings indicated a significant improvement in mobile eHL (t114=3.391, P=.001) and mHealth literacy (mHL, a subconcept of mobile eHL; t114=3.801, P<.001) within the intervention group, whereas no such improvement was observed in the control group. The chi-square values from the McNemar test underscored that individuals with uncontrolled diabetes (HbA1c≥7%) in the intervention group exhibited more improvement compared with the control group. The generalized estimating equations model unveiled a significant difference in the change of general mHL in the intervention group (β=1.91, P=.047) and self-care behavior in the control group from T0 to T2 (β=-8.21, P=.015). Despite being small, the effect sizes for mobile eHL (d=0.49) and HbA1c (d=0.33) in the intervention group were greater than those in the control group (d=0.14 and d=0.16, respectively). ConclusionsThe implementation of a mobile eHL education intervention demonstrates a positive influence on the familiarity of patients with T2D regarding health technology, leading to favorable glycemic outcomes. While additional studies are warranted for a more comprehensive understanding, this program emerges as a promising solution for enhancing patients' uptake of digital health technology.